교육 전문가들이 인식한 앙트러프러너십 개념과 교육 방향 - 김미호(Miho Kim); 박수홍(Suhong Park); 강주현(Juhyun Kang) (평생학습사회, 2023)
본 연구는 4차 산업혁명의 흐름 속에서 교육 연구자들과 현장 교육자들이 앙트러프러너십의 개념과 교육 방향성에 대해 어떤 인식을 하고 있는지 살펴보고자 하였다. 이를 위해 모 대학 연구센터의 <앙트러프러너십 교육 퍼실리테이터 양성과정> 프로그램에 참여한 교육 연구자 및 현장 교육자의 집담회 자료를 수집하고 참여자들의 진술을 분석하였다. 먼저, 앙트러프러너십 개념에 대한 교육 전문가의 인식은 개인적 측면에서는 ‘보편적 핵심 역량’, ‘주체적 성장 동력’, ‘실천 역량’이라는 3개의 상위범주로, 사회적 측면에서는 ‘집단 프로세스 기반 활동’, ‘문제 해결을 통한 사회혁신’, ‘창의 융합적 사회 가치 창출’이라는 3개의 상위범주로 분석되었다. 다음으로, 앙트러프러너십 교육 방향성에 대해서는 전체적으로는 체계적 프로세스를 기반으로 한 차별적인 프로그램 개발과 역동적 조직 문화와 퍼실리테이션의 강화를 들었다. 또한 사례연구 단계, 공감적 문제 발견 단계 등 프로세스 단계에 따라 다양한 방법론적 방향을 제안하였다. This study aimed to examine the awareness level of education researchers and field educators regarding the concept of entrepreneurship and the direction of education in the flow of the Fourth Industrial Revolution. Consequently, the conference data of education researchers and field educators who participated in the <Entrepreneurship Education Leader Training Course> program of the University Research Center were collected and analyzed. First, education experts' perceptions of the concept of entrepreneurship were divided into three upper categories in the personal aspect: “universal core competency,” “independent growth engine,” and “practice competency.” Subsequently, it was analyzed into three upper categories in the social aspect: “group process-based activities,” “social innovation through problem-solving,” and “creation of creative convergence social value.” In addition, various methodological directions were proposed according to the process stages, such as the case-study stage and the empathetic problem-discovery stage. KCI Citation Count: 1